Effectiveness of Neurofunctional Physical Therapy on the Quality of Sleep of Individuals with Parkinson's Disease: Case Series - Souza, Rogério José de; Shigaki, Isabela Andrelino de Almeida; Terra, Marcelle Brandão; Barboza, Natália Mariano; Bueno, Maria Eduarda Brandão; Mesas, Arthur Eumann; Smaili, Suhaila Mahmoud (Sleep Science, 2023)
Objective Sleep disorders are disabling and highly prevalent comorbidities in Parkinson's disease (PD). This study's objective was to verify the effectiveness of neurofunctional physiotherapy in sleep quality, objectively and subjectively assessing it among individuals with PD.Methods A sample of individuals with PD was assessed before and after 32 physiotherapy sessions and three months later (follow-up). The following instruments were used: Pittsburgh Sleep Quality Index (PSQI); Epworth Sleepiness Scale (ESS); Parkinson's Disease Sleep Scale (PDSS), and actigraphy.Results Nineteen individuals aged 67.37 years old ( ±  8.03) on average were included. No differences were found in any of the variables measured by the actigraphy or the ESS. Improvement was found from pre- to post-intervention in terms of nocturnal movements (p = 0.04; d = 0.46) and total score (p = 0.03; d = 0.53) obtained on the PDSS. Improvement was also found in the PDSS sleep onset/maintenance domain (p = 0.001; d = 0.75) between pre-intervention and follow-up. The participants' total score obtained in the PSQI improved from pre- to post-intervention (p = 0.03; d = 0.44). Significant differences were found in nighttime sleep (p = 0.02; d = 0.51) and nocturnal movements (p = 0.02; d = 0.55), and in the PDSS total score (p = 0.04; d = 0.63) between pre- and post-intervention when only the poor sleepers subgroup (n = 13) was considered, while improvements were found in sleep onset/maintenance (p = 0.003; d = 0.91) between pre-intervention and follow-up.Discussion Neurofunctional physiotherapy was ineffective in improving objective parameters of sleep but was effective in improving the perception of sleep quality subjectively assessed among individuals with PD, especially those who perceived themselves to be poor sleepers.
Keywords: Physical Therapy Specialty; Parkinson Disease; Sleep; Actigraphy; Rehabilitation